MOCCCDTA-based Current Mode Tunable Universal Biquad Filter for Bluetooth Applications - Jyoti Sharma; Shantanu Chakraborty (Institute of Advanced Engineering and Science, 2016)
In the last decade, there has been much effort to reduce the supply voltage of electronic circuits due to the demand for portable and battery-powered equipment. Since a low-voltage operating circuit becomes necessary, the current-mode technique is ideally suited for this purpose more than the voltage-mode one. In this paper, performance of multi output current controlled current differencing transconductance amplifier (MOCCCDTA) is evaluated using 180nm, 90nm and 45nm CMOS technology. It is found that the 45nm CMOS-basedMOCCCDTA provides highest frequency i.e. 33GHz. Further a Universal biquad filter has been designed using a single MOCCCDTA as an active element and two capacitors. Filter offers high frequency in GHz. Tunability of all the filter outputs with respect to a bias current has been analyzed. The tunability of the filter circuit for Bluetooth applications is also shown in this work. The performances of MOCCCDTA circuit and Universal biquad filter are illustrated by HSPICE. The simulation results are found to be in agreement with the theoretical predictions.